Effectiveness of Mind-Map Based-Project Based Learning and Concept Map Based-Project Based Learning on Environmental Science Course at Universitas Lancang Kuning Pekanbaru - Al Khudri Sembiring; Hasruddin Hasruddin; Fauziyah Harahap (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research aims to determine the effectiveness of three treatments of learning models, i.e. project based learning based on mind maps, project based learning using the concept map, and conventional learning method on mastery the concept of environmental science course. Research was done at Universitas Lancang Kuning Peknbaru. Research method was a quasi experiment with pretest and posttest design. The participants were second semester students of Biology Education in academic year 2014 and 2015, consisting of three classes. Class B was the experiment 1 (20 students), Class B was experiment 2 (23 students), and class C was control (20 students). The cognitive knowledge of students was tested by assessment of cognitive test (C1-C6). Data was normal and homogeneous. Data analysis was analysis covariat (anacova) and the least significant difference (LSD). The results showed that the treatments significantly influenced the concept mastery. The ability of mastery of the concept of a student who study with project based learning using mind map was (81,17 ± 12,72) or not differ significantly with the concept map based-project based learning (78,84 ± 12,29) (P = 0,521) and conventional learning. There are significant differences between the mastery of the concept of (67,00 ± 10.8) (P = 0.00). Based on the results of the study it can be concluded that Concept Map based- Project based learning is more effective than other treatments.Keywords: Mind map, Concept map, Mastery of the Concept of, Environment.